Analysis of the Properties of 44 ABC Transporter Genes from Biocontrol Agent Trichoderma asperellum ACCC30536 and Their Responses to Pathogenic Alternaria alternata Toxin Stress - Hua-Ying Du; Yu-Zhou Zhang; Kuo Liu; Pei-Wen Gu; Shuang Cao; Xiang Gao; Zhi-Ying Wang; Zhi-Hua Liu; Ze-Yang Yu (Current Issues in Molecular Biology, 2023)
ATP-binding cassette (ABC) transporters are involved in transporting multiple substrates, such as toxins, and may be important for the survival of Trichoderma when encountering biotic toxins. In this study, genome searching revealed that there are 44 ABC transporters encoded in the genome of Trichoderma asperellum. These ABC transporters were divided into six types based on three-dimensional (3D) structure prediction, of which four, represented by 39 ABCs, are involved in transport and the remaining two, represented by 5 ABCs, are involved in regulating translation. The characteristics of nucleotide-binding domain (NBD) are important in the identification of ABC proteins. Even though the 3D structures of the 79 NBDs in the 44 ABCs are similar, multiple sequence alignment showed they can be divided into three classes. In total, 794 motifs were found in the promoter regions of the 44 ABC genes, of which 541 were cis-regulators related to stress responses. To characterize how their ABCs respond when T. asperellum interact with fungi or plants, T. asperellum was cultivated in either minimal media (MM) control, C-hungry, N-hungry, or poplar medium (PdPap) to simulate normal conditions, competition with pathogens, interaction with pathogens, and interaction with plants, respectively. The results show that 17 of 39 transport ABCs are highly expressed in at least one condition, whereas four of the five translation-regulating ABCs are highly expressed in at least one condition. Of these 21 highly expressed ABCs, 6 were chosen for RT-qPCR expression under the toxin stress of phytopathogen Alternaria alternata, and the results show ABC01, ABC04, ABC05, and ABC31 were highly expressed and may be involved in pathogen interaction and detoxifying toxins from A. alternata.